Relations among birth condition, maternal condition, and postnatal growth in captive common marmoset monkeys (Callithrix jacchus) - Tardif, Suzette D.; Bales, Karen L. (American journal of primatology, 2004)
The present study characterizes the relations among maternal condition, litter size, birth condition, and growth in body weight for a population of common marmosets. The subjects of the study were marmosets born into a single colony between 1994 and 2001. Three sets of analyses were conducted to answer the following questions: 1) Is there a relationship between litter size, maternal condition, and birth condition? In the study population, maternal body weight, maternal age, litter size, and birth condition were related in a complex fashion. Birth weight and prenatal long‐bone growth, as reflected in knee–heel length, were both related to maternal age, with older mothers supporting higher prenatal growth. Age and maternal condition appeared to interact as determinants of long‐bone growth, as the combination of older and larger mothers resulted in significantly longer knee–heel lengths in their offspring. 2) Is there a relationship between birth condition or maternal condition and subsequent growth or final adult size? The early growth rate in this population was similar to early growth rates reported for three different marmoset colonies, suggesting that early growth may be relatively inflexible in this species. However, within this population, the variation that did occur in early growth rate was related to birth weight and maternal weight. Later growth and adult weight were related to birth weight and litter size: small twin infants displayed slower later growth rates and were smaller as adults than twins that began life at a higher birth weight, while the birth weight of triplets was not related to adult size. In these marmosets, small infants that were the result of increased litter size differed from small infants whose small birth size resulted from other factors. This reinforces the proposal that the causes of low birth weight will be relevant to the development of the marmoset as a model of prenatal environmental effects. Am. J. Primatol. 62:83–94, 2004. © 2004 Wiley‐Liss, Inc.